2003
DOI: 10.1046/j.1471-4159.2003.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of rat 5‐HT2A receptors using antisense oligonucleotides

Abstract: We studied the effects in rats of a 6-day intracerebroventricular (i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…Using factor analysis, the authors found no significant difference between wildtype and 5-HT 2A knockout mice in anxiety-like behavior. Similar findings were reported by Van Oekelen et al [2003] using ASODN to 5-HT 2A -R, leading the authors to hypothesize that downregulation of the functional 5-HT 2A receptors may cause an imbalance in the ratio of the different 5-HT receptor subtypes. Thus, the increased serotonergic transmission due to the surgical implantation of the cannulae may lead to greater activation of receptors other than the 5-HT 2A subtype, resulting in increased locomotor activity.…”
Section: Discussionsupporting
confidence: 79%
“…Using factor analysis, the authors found no significant difference between wildtype and 5-HT 2A knockout mice in anxiety-like behavior. Similar findings were reported by Van Oekelen et al [2003] using ASODN to 5-HT 2A -R, leading the authors to hypothesize that downregulation of the functional 5-HT 2A receptors may cause an imbalance in the ratio of the different 5-HT receptor subtypes. Thus, the increased serotonergic transmission due to the surgical implantation of the cannulae may lead to greater activation of receptors other than the 5-HT 2A subtype, resulting in increased locomotor activity.…”
Section: Discussionsupporting
confidence: 79%
“…The psychedelic 5-HT 2A/2C receptor agonist 2,5-dimethoxy-4-iodoamphetamine (DOI) has been shown to affect locomotor activity in mice (Gonzalez-Maeso et al, 2007; Halberstadt et al, 2009, 2013) and rats (Krebs-Thomson et al, 1998; Van Oekelen et al, 2003; Marona-Lewicka et al, 2005). Low doses of DOI significantly increase locomotor activity, an effect that is absent in 5-HT 2A knockout mice (Halberstadt et al, 2009).…”
Section: Pharmacological Models Of Psychosis and Antipsychotic Drug Amentioning
confidence: 99%
“…More recently, increased threshold to kainic acid-induced seizures was observed in mice with genetically increased 5-HT levels ( Tripathi et al, 2008 ). These findings are corroborated by data showing that mice lacking the 5-HT 1A - ( Sarnyai et al, 2000 ; Parsons et al, 2001 ), 5-HT 2C - ( Applegate and Tecott, 1998 ), 5-HT 4 - ( Compan et al, 2004 ) and, 5-HT 7 -Rs ( Witkin et al, 2007 ), but also rats knocked-down for the 5-HT 2A -Rs by antisense oligonucleotide treatment ( Van Oekelen et al, 2003 ) are extremely susceptible to chemical and electrical-induced seizures. Nevertheless, since only 5-HT 2C -R KO mice are prone to spontaneous death from seizures ( Tecott et al, 1995 ), and seizures have not been reported with pharmacological blockade of different 5-HT-Rs, adaptive changes involving different mechanisms may play a role in the low seizure thresholds observed in 5-HT-R KO mice.…”
Section: The 5-ht 2a -Rs In the Regulation Of Epilmentioning
confidence: 54%